2007
DOI: 10.1152/ajpregu.00400.2006
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring hypertension in New World nonhuman primates: potential role of the perifornical hypothalamus

Abstract: Smith OA, Astley CA. Naturally occurring hypertension in New World nonhuman primates: potential role of the perifornical hypothalamus. Am J Physiol Regul Integr Comp Physiol 292: R937-R945, 2007. First published October 5, 2006; doi:10.1152/ajpregu.00400.2006.-Hypertension is a prominent underlying factor in the genesis of cardiovascular-related morbidity and mortality. A major impediment to the investigation into the causes of the disease is the paucity of naturally occurring animal models of the disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 23 publications
7
24
0
2
Order By: Relevance
“… in Cebus apella . In the physical restraint group, the blood pressure values were higher compared to the resting pressure . This probably happened because of the stress caused by restraint, which causes the release of catecholamine, thereby increasing the values of BP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“… in Cebus apella . In the physical restraint group, the blood pressure values were higher compared to the resting pressure . This probably happened because of the stress caused by restraint, which causes the release of catecholamine, thereby increasing the values of BP.…”
Section: Discussionmentioning
confidence: 87%
“…HR was considered high in all protocols tested compared to data obtained by Smith and Astley in Aotus nancymai in resting condition. However, the values found confirm what was described in other studies for anesthetized Aotus azarae infulatus .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyopathy has a decreased prevalence in owl monkeys that have not been in captivity for an extended period of time [13]. A previous study indicated that owl monkeys react to laboratory disturbances with significant, prolonged elevations in blood pressure [21] The study of cardiomyopathy in owl monkeys is not only important in maintaining a self-sustaining breeding colony, but it may be a useful model for human cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Os valores da frequência cardíaca (FC) observados neste trabalho estão de acordo com os encontrados por Baer (1994), Rajendra et al (2010) e Galante (2013) em Aotus submetidos à anestesia, no entanto foram considerados elevados em comparação aos dados obtidos por Smith & Astley (2007) em Aotus nancymai em condição de repouso. Sabe-se que, tanto os anestésicos utilizados quanto fatores estressantes como a contenção física elevam a FC de forma considerável (Smith & Astley 2007).…”
Section: Discussionunclassified
“…Sabe-se que, tanto os anestésicos utilizados quanto fatores estressantes como a contenção física elevam a FC de forma considerável (Smith & Astley 2007).…”
Section: Discussionunclassified